(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article’s objective is to show teachers how to retain the exercises so well that they may use them with their students, modifying the tasks to fit the students’ abilities. More crucially, it spreads the myth that teachers’ professional development is dependent on obtaining new knowledge and resources from other sources, which discourages teachers from feeling in control of their own professional development